STUDI PENGGUNAAN ANTIMALARIA PADA PENDERITA MALARIA DI INSTALASI RAWAT INAP BLU RSUP Prof. Dr. R. D. KANDOU MANADO PERIODE JANUARI 2013-MEI 2013 - Rumagit, Novia Akwila; Tjitrosantoso, Heedy; Wiyono, Weny I (PHARMACON, 2013)
ABSTRACTMalaria is parasite infectious diseases group of Plasmodium which live in human red bloodcell and can be transmitted by a female Anopheles bites. Malaria were classified as one of themost dangerous infectious diseases which cause death. In North Sulawesi, malaria is anendemic diseases because it’s a tropical area, and so susceptible to this disease. Treatment ofmalaria is to obtain clinical and parasitologic recovery. The objectives of this research wereto find out the characteristic of malaria and the use of antimalaria drugs on patient withmalaria. This research is a descriptive survey with retrospective sampling on 68 medicalrecord of patient with malaria treatment. Obtained data shows that there are three variant ofmalaria, falciparum malaria (66,2%), vivax malaria (26,5%), mixed malaria (7,4%).Artesunat-amodiakuin-primakuin in an ACT (Artemisinin Combination Treatment) thatmostly used as malaria drug.Keywords: Plasmodium, red blood cell, malaria, antimalaria